Thrombosis Journal - Ozaki, Yukio; ten Cate, Hugo
Thrombosis Journal  is an open-access journal that publishes original articles on aspects of clinical and basic research, new methodology, case reports and reviews in the areas of thrombosis. Topics of particular interest include the diagnosis of arterial and venous thrombosis, new antithrombotic treatments, new developments in the understanding, diagnosis and treatments of atherosclerotic vessel disease, relations between haemostasis and vascular disease, hypertension, diabetes, immunology and obesity.